First fluorescein liquid crystals: synthesis, mesomorphic and fluorescence properties of fluorescein-triphenylene dimers. Issue 12 (25th September 2020) - Fan, Tianwen; Shi, Rongxin; Tang, Huaying; Guo, Hongyu; Yang, Fafu
ABSTRACT: This paper reported not only the first fluorescein liquid crystals but also revealed the influence of peripheral alkyl chains on mesomorphic properties and photophysical properties. Novel fluorescein-triphenylene dimers 4a–4f with different alkyl chains were designed and synthesised in yields of 76–83%. Samples 4a, 4b, 4c and 4d with CH3 and C4 H9 exhibited the columnar mesophase but samples 4e and 4f with C8 H17 showed no mesophase. The longer alkyl chains on fluorescein units resulted in the lower phase transition temperature. The too long alkyl chain destroyed the liquid crystalline behaviour. Their fluorescence quantum yields were as high as 0.78–0.87 in CH2 Cl2 solution and 0.11–0.17 in solid states. The longer alkyl chains leaded to the higher emission efficiencies. GRAPHICAL ABSTRACT: uf0001